DEVELOPING HOTS-BASED MATHEMATICS ASSESSMENT INSTRUMENTS TO IMPROVE CRITICAL THINKING SKILLS OF PROSPECTIVE ELEMENTARY SCHOOL TEACHERS - Amrina, Zulfa; Sari, Syafni Gustina; Alfino, Joni; Amelia, Puspa (FKIP Universitas Muhammadiyah Tangerang, 2024)
The current reality is that most teachers have not developed their students' Higher Order Thinking (HOTS) skills. This is because the teachers themselves do not understand HOTS well. This research aims to develop HOTS-based mathematics assessment instruments for prospective elementary school teachers. The type and model of research conducted is research and development (R n D), Borg & Gall model. The product developed is a 10-item HOTS question. The questions that have been compiled are validated by three validators. Valid questions were tested on students who took Mathematics Learning courses. The trial was conducted with the aim of determining the quality of the instrument using classical test theory, namely validity, reliability, difficulty index, and distinguishing power. The results showed that the HOTS-based mathematics assessment instrument met the criteria of a quality instrument, namely very valid, high reliability, with good differentiation and difficulty levels. Thus, the instrument developed is suitable to be used to measure the HOTS ability of prospective teacher students. From the results of the test analysis, it was found that the students' ability to solve HOTS-based problems obtained an average of 74.65 was in the moderate category and the results of the analysis of students' critical thinking skills obtained 62.89% also in the moderate category. So it can be concluded that students' ability to solve HOTS-based questions is directly proportional to students' critical thinking skills. Thus, it can be concluded that HOTS-based assessment instruments can improve the critical thinking skills of prospective elementary school teachers.